2020
DOI: 10.1136/medethics-2019-105597
|View full text |Cite
|
Sign up to set email alerts
|

Trust and consent: a prospective study on parents’ perspective during a neonatal trial

Abstract: ObjectiveThis study aimed to describe how parents and physicians experienced the informed consent interview and to investigate the aspects of the relationship that influenced parents’ decision during the consent process for a randomised clinical trial in a tertiary neonatal intensive care unit (NICU). The secondary objective was to describe the perspectives of parents and physicians in the specific situation of prenatal informed consent.SettingSingle centre study in NICU of the Centre Hospitalier Intercommunal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…We found higher levels of trust in medical researchers among enrolled parents compared with parents who declined, but no difference in trust in clinicians on 2 trust scales. The higher trust in medical researchers among enrolled parents is consistent with reflections of experienced NICU clinical researchers 15 as well as interview 7 and survey 16 studies of parents considering research participation.…”
Section: Trustmentioning
confidence: 83%
See 2 more Smart Citations
“…We found higher levels of trust in medical researchers among enrolled parents compared with parents who declined, but no difference in trust in clinicians on 2 trust scales. The higher trust in medical researchers among enrolled parents is consistent with reflections of experienced NICU clinical researchers 15 as well as interview 7 and survey 16 studies of parents considering research participation.…”
Section: Trustmentioning
confidence: 83%
“…[3][4][5][6] There are limited data to explain how parents decide whether to participate in neonatal clinical trials. Previous research has struggled to include the views of those who decline neonatal research 7,8 with only a few exceptions. 9,10 Low enrollment rates within neonatal clinical trials diminish the quality of data collected and limit the generalizability of results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCPs indicated that the trusting relationship with parents is one of the main reasons to consent, which is in line with the available literature. For example, it was reported that information written in the IC form did not always support parents' understanding ( 47 ). Similarly, HCPs raised that IC documents are often difficult to understand, due to scientific and legal information.…”
Section: Discussionmentioning
confidence: 99%
“…3 An important determining factor to the success of the informed consent process requires diligent communication and the establishment of trust between the medical team and parents, wherein ''effective interactions,'' if possible, become essential. 4 This concept establishes the focus of the research team to engage in a long-term relationship with parents beyond the initial consent approach that provides a long consideration phase and the opportunity to ask questions or otherwise interact with embedded clinical research nurses (CRNs) in the NICU.…”
Section: Introductionmentioning
confidence: 99%